Platelets, Macrophages, and Thromboinflammation in Chagas Disease - Choudhuri S; Garg NJ (Dove Medical Press, 2022)
Subhadip Choudhuri, Nisha J Garg Department of Microbiology and Immunology, Institute for Human Infections and Immunity, University of Texas Medical Branch, Galveston, TX, USACorrespondence: Nisha J Garg, Email nigarg@utmb.eduAbstract: Chagas disease (CD) is a major health problem in the Americas and an emerging health problem in Europe and other nonendemic countries. Several studies have documented persistence of the protozoan parasite Trypanosoma cruzi, and oxidative and inflammatory stress are major pathogenic factor. Mural and cardiac thrombi, cardiac arrhythmias, and cardiomyopathy are major clinical features of CD. During T. cruzi infection, parasite-released factors induce endothelial dysfunction along with platelet (PLT) and immune-cell activation. PLTs have a fundamental role in maintaining hemostasis and preventing bleeding after vascular injury. Excessive activation of PLTs and coagulation cascade can result in thrombosis and thromboembolic events, which are recognized to occur in seropositive individuals in early stages of CD when clinically symptomatic heart disease is not apparent. Several host and parasite factors have been identified to signal hypercoagulability and increase the risk of ischemic stroke in early phases of CD. Further, PLT interaction with immune cells and their role in host defense against pathogens and inflammatory processes have only recently been recognized and evolving. In the context of parasitic diseases, PLTs function in directly responding to T. cruzi infection, and PLT interactions with immune cells in shaping the proinflammatory or immunoregulatory function of monocytes, macrophages, and neutrophils remains elusive. How T. cruzi infection alters systemic microenvironment conditions to influence PLT and immune-cell interactions is not understood. In this review, we discuss the current literature, and extrapolate the mechanistic situations to explain how PLT and innate immune cell (especially monocytes and macrophages) interactions might be sustaining hypercoagulability and thromboinflammation in chronic CD.Keywords: Chagas disease, coagulopathy, inflammation, macrophage activation, platelets, thrombosis